A cadaveric study on variations in branching pattern of external carotid artery - Devadas, Deepa (Anat Cell Biol, 2018)
Variations in the vascular anatomy of the carotid triangle have been reported in current scientific literature. The carotid arteries, being the major feeding arteries of the head and neck deserve special importance and protection from iatrogenic injury during radiological evaluations and surgical interventions. The present study was carried out over a period of 4 years from 2012–2016 to assess the variant anatomy of external carotid artery. The external carotid artery and its branches were dissected bilaterally in 40 formalin embalmed cadavers. The external carotid artery was traced from its origin to termination and variations in the branching pattern as well as the level of the carotid bifurcation were observed and analysed. A higher carotid bifurcation was observed in 25% cases. The linguofacial trunk was the commonest variation noted in the branching pattern seen in 20% cases. A single case of unilateral thyrolinguofacial trunk was also observed. The external carotid artery gave rise to accessory branches in 7.5% cases namely the superior laryngeal, accessory ascending pharyngeal and masseteric branches. A slender branch to the internal jugular vein was also observed in one case. These findings may provide further insight into the understanding of the vascular anatomy of the carotid triangle to the curious student, the discerning radiologist and the vigilant surgeon to avert complications and help improve overall treatment outcome.